Exploring Unique Local Cultural Values: Strategies for Utilizing Tourism Potential - Suwarti Suwarti; Aurilia Triani Aryaningtyas; Tiara Sanika L. Putriningsih; Flores Harliesyahputra Laia (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
Penadaran Village in Grobogan Regency, Central Java, Indonesia, possesses a unique and vibrant cultural heritage that remains largely untapped for tourism development. This research aimed to identify the distinctive local cultural values of Penadaran, analyze their potential for tourism, and formulate strategies for sustainable cultural tourism while preserving local wisdom. Employing a qualitative approach involving observations, interviews, and document analysis, the study engaged local community leaders, policymakers, and tourism stakeholders. The findings revealed Penadaran's rich traditions, such as the